2015
DOI: 10.1007/s00436-015-4442-y
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic diversity found in coprolites of camelids during the Holocene

Abstract: Knowledge of parasitic infections to which fauna was exposed in the past provides information on the geographical origin of some parasites, on the possible dispersal routes and for archaeological fauna on the potential zoonotic risk that human and animal populations could be exposed. The aim of the present study was to examine the gastrointestinal parasite present in camelid coprolites collected from the archaeological site Cerro Casa de Piedra, cave 7 (CCP7), Patagonia, Argentina. Coprolites were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
2
27
0
3
Order By: Relevance
“…Other morphotype was comparable to Eucoleus sp. and the third morphotype had not matching with any capillariid described in camelids until that time [18]. An study done in this region showed once more the same morphotype compatible with Calodium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Other morphotype was comparable to Eucoleus sp. and the third morphotype had not matching with any capillariid described in camelids until that time [18]. An study done in this region showed once more the same morphotype compatible with Calodium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Los huevos hallados presentan un tinte pardo, similar a los huevos de L. chavezi (McKenna, 2006). En Patagonia, existen solo dos registros de Lamanema en L. guanicoe pero numerosos reportes de huevos similares en coprolitos de camélidos (Fugassa, 2007;Taglioretti et al 2015). La frecuencia de estos molineidos en el contexto arqueológico de cuevas y la baja prevalencia actual puede asociarse a: 1) un reemplazo, a partir de la colonización europea, por molineidos que también ocupan el intestino delgado en el ganado.…”
Section: Resultados Y Discusiónunclassified
“…Dentro del área principal excavada, todos los niveles contuvieron coprolitos atribuibles a camélidos o cérvidos. Hasta la fecha se examinaron coprolitos, presumiblemente, de camélidos de diversos niveles del sector principal excavado (Fugassa, 2007;Taglioretti, 2008;Taglioretti et al 2015;Taglioretti, 2015) y de los niveles II y III del área secundaria excavada últimamente (Taglioretti, 2015). Con el objetivo de completar la información parasitológica sobre camélidos en el sector principal excavado de CCP7, se examinaron coprolitos pertenecientes a nueve niveles estratigráficos, ocho de los cuales permanecían inexplorados (Tabla 1) y que contenían coprolitos asignables a camélidos.…”
Section: Materiales Y Métodosunclassified
“…Asimismo, en los niveles estratigráficos 3 y 4 se identificaron huevos larvados con buena conservación y que corresponderían a Nematodirus sp., probablemente Nematodirus spathiger debido a las características de las larvas en el tercer estadio de desarrollo (L3) que fueron halladas en los coprolitos (Taglioretti et al 2017). Nematodirus spathiger es un helminto parásito de ovejas (Soulsby, 1987), su presencia no ha sido reportada en estudios previos realizados sobre muestras prehispánicas de camélidos de Patagonia (Fugassa, 2007;Taglioretti et al 2015;Amalfitano et al 2017; entre otros). Asimismo, tampoco se ha reportado N. spathiger en muestras arqueológicas de camélidos de otras regiones (Leguía & Casas, 1999).…”
Section: Introductionunclassified